The Influence of Intellectual Capital on Financial Performance and its Impact on Company Value - Raja gukguk, Maria Cristina; Putra, Wirmie Eka; Mansur, Fitrini (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to assess how intellectual capital affects financial success and related consequences for corporate value empirically and to present relevant data. Data is collected using documentation procedures. Descriptive statistics and partial least squares (PLS), a type of variance- or component-based structural equation modeling, were used to analyze the data. The software employed in this study was called SmartPLS. The study's findings show a significant relationship between intellectual capital and financial performance. Furthermore, studies have shown that a company's financial performance has a favorable and considerable impact on its worth. Intellectual capital has a major and beneficial impact on a company's worth. Lastly, there's a chance that financial performance will act as a bridge between business value and intellectual capital.